Chopin on the cinema screen. Aesthetic and cultural determinants - Kornacki, Krzysztof (Interdisciplinary Studies in Musicology, 2018)
As with most film subjects, the way Chopin has been presented in the cinema has been the result of a particular poetic (depending on the genre) and cultural context. The author classifies cinematographic Chopinalia on the basis of the former determinant, although without neglecting entirely, in some sections of the text, to treat film as a text of culture. The clear majority of documentary and educational films about Chopin have been made in Poland (as a form of promotion for the country, which does not boast too many icons of world culture). For both aesthetic and cultural reasons, the boundary between documentary and educational film has become blurred. Historical documentaries have used the same iconographic material, film shots and utterances, and also - for the purposes of musical illustration - the same Chopinworks as educational films. Cultural considerations have affected the thematic restrictions in respect to silver screen discourse about Chopin: in both genres, it reflects a rather stereotypical approach to the composer’s life story, with no room for the “Chopin mysteries” (e.g. his fascination with Tytus Woyciechowski) that have long been addressed in the literature. In experimental and animated film, the accent has been shifted - in keeping with the essence of those genres - from Chopin’s biography to his music. Nevertheless, here too the pressure of cultural (national) context has determined the choice of film material accompanying particular works. At the same time, experimental films have become anti-war or political films (as in the case of Eugeniusz C^kalski’s Utwory Chopina w kolorze [Chopin’s works in colour], from 1944 or Andrzej Panufnik’s Bailada f moll [Ballade in F minor], from 1945), whilst the presentation of Chopin’s music in animated films has been full of iconographic clichés and pleonasms (a Mazovian landscape with cleft willows, carriages speeding along in the background, dancing ballerinas, falling leaves and so on), creating a schematic visual code that is automatically associated with the compositions of the brilliant Pole. By way of contrast, it is worth emphasising that a few foreign experimental films (Max Ophiils’s La Valse Brillante de Chopin, Germaine Dulac’s Dysk 927) have illustrated Chopin’s music with images of “universal” objects (piano, gramophone, rain) associated more with music than with feelings, and not with Poland. The dozen or so feature films about Chopin have mainly belonged to popular cinema. For that reason, in the overwhelming majority of cases, the film-makers have turned to biographical facts which possess a suitable dramatic potential. Feature films about Chopin have treated history as a background - a costume in which to dress a tale about universal cultural myths: the myth of love (the relationship with George Sand, which has dominated Chopin films), the pseudo-Romantic myth of the great artist and the patriot myth (prime examples being Charles Vidor’s A Song to Remember and Jerzy Antczak’s Chopin. Pragnienie miłości [Chopin. Desire for love]). Some films - albeit few in number - have adopted a different strategy. One such picture attempted to exploit Chopin’s life story to exemplify Marxist historiosophy and a socialist- realist poetic (Aleksander Ford’s Młodość Chopina [Chopin’s youth]); another- Andrzej Żulawski’s Błękitna nuta [La note bleue] - is a truly original picture about the composer and, like almost every original film, tells us as much about the director as about Chopin himself.